La bibliografia di A. Rimoldi: una introduzione e un primo elenco bibliografico - Picasso, Giorgio (La Scuola Cattolica, 2025)
Together with a first bibliography of mgr. Rimoldi, for the completion of which the author gives important indications, he proposes a reading of his scientific production, offering insights to understand the maturation, the characteristics and the guidance on the method that characterise the way to do history of mgr. Rimoldi.